EVALUATION OF SPINOPELVIC BALANCE IN PATIENTS WITH THORACOLUMBAR JUNCTION FRACTURES SURGICALLY TREATED WITH SCHANZ SCREWS - JOÃO GABRIEL BELEGANTE SCALABRIN; ANDRE LUIS SEBBEN; ÁLYNSON LAROCCA KULCHESKI; PEDRO GREIN DEL SANTORO; FELIPE DE NEGREIROS NANNI; JOÃO ELIAS BRAGA; XAVIER SOLER I GRAELLS (Coluna/Columna, 2025)
ABSTRACT Objective: To evaluate the spinopelvic alignment in patients with thoracolumbar junction fractures surgically treated with Schanz screws and to conduct an epidemiological assessment of these patients. Methods: A longitudinal and retrospective study was conducted, analyzing the electronic medical records and imaging files of patients who suffered thoracolumbar junction fractures (T11-L2) and underwent surgery using the Schanz screw technique between January 2017 and January 2021. Spinopelvic balance measurements (PI; LL; PT; SS; PI-LL; L4S1) and epidemiological data such as age, sex, fracture type, and trauma mechanism were analyzed. Radiographic assessments were performed at the initial postoperative period (POI) and 12 months postoperatively (PO 12m) using the Surgimap® system. Results: A total of 35 patients were analyzed. The most prevalent fracture type was AO A4, with a fall from height being the primary trauma mechanism. There was a significant increase in lower lumbar lordosis (L4S1) between POI and PO 12m (8.5°), as well as in PI-LL (8.9°), both with statistical significance. Conclusion: The fixation of thoracolumbar junction fractures with Schanz screws restored normal spinopelvic balance 12 months postoperatively. Males were the most prevalent group, and a fall from height was the main trauma mechanism. Burst fractures were the most common among these injuries. Level of Evidence II; Longitudinal and Retrospective Study.